Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.254
|View full text |Cite
|
Sign up to set email alerts
|

Prompt-free and Efficient Few-shot Learning with Language Models

Abstract: Current methods for few-shot fine-tuning of pretrained masked language models (PLMs) require carefully engineered prompts and verbalizers for each new task to convert examples into a cloze-format that the PLM can score. In this work, we propose PERFECT, a simple and efficient method for few-shot fine-tuning of PLMs without relying on any such handcrafting, which is highly effective given as few as 32 data points. PERFECT makes two key design choices: First, we show that manually engineered task prompts can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…For the language tasks, we use PERFECT, a recent adaptation method from Mahabadi et al [48] 9 , which inserts an adapter layer after the feed-forward block of each transformer layer of a RoBERTa-Large model, an early FM consisting of 355M parameters. This results in 3.3M trainable parameters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the language tasks, we use PERFECT, a recent adaptation method from Mahabadi et al [48] 9 , which inserts an adapter layer after the feed-forward block of each transformer layer of a RoBERTa-Large model, an early FM consisting of 355M parameters. This results in 3.3M trainable parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Foundation Models We use popular existing FMs and FM adaptation techniques in our evaluations. In particular, we use simple zero-shot [58], in-context learning [10] and lightweight tuning [29,48] methods (defined in Section 3). We are inspired by work on versatile FM systems with natural language interfaces [37,77], though instead of ML methods, our focus is the consequences of these FM capabilities on privacy.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Mahabadi et al [28] found that PEFT can outperform standard fine-tuning in the low-resource setting. In concurrent work, Mahabadi et al [76] compare PEFT to the use of discrete prompts (e.g. PET [70]) during few-shot fine-tuning and find that PEFT compares favorably.…”
Section: Related Workmentioning
confidence: 99%